Thermal aging effects on the microstructure of Nb-bearing nickel based superalloy weld overlays using ultrasound techniques - Albuquerque, Victor Hugo Costa de (2012)
Secondary phases such as Laves and carbides are formed during the final stages of solidification of the nickel based superalloy Inconel 625 coatings deposited during the gas tungsten arc welding (GTAW) cold wire process. However, when aged at high temperatures, other phases can precipitate in the microstructure, like the c00 and d phases. The aim of this work was to evaluate the different phases formed during thermal aging of the as-welded material through ultrasound inspection, as well as the influence of background echo and backscattered ultrasound signals on the computational classification of the microstructures involved. The experimental conditions employed an aging temperature of 650 C for 10, 100 and 200 h. The ultrasound signals were acquired using transducers with frequencies of 4 and 5 MHz and then processed to determine the ultrasound velocity and attenuation, as well as to study the background echo and backscattered signals produced by wave propagation. Both signal types were used to study the effectiveness and speed for classifying the secondary phases, using detrended fluctuation analysis and the Hurst method in the signal pre-processing and the Karhunen–Loève Transform in the classification of the microstructures. The ultrasound signals and the signal processing tools used were considered sufficiently sensitive, fast and accurate in the detection and classification of the microstructures in the aswelded and aged Inconel 625 alloy using this nondestructive technique.